Community Unionism in Africa: The Case of Mozambique - Dibben, Pauline; Nadin, Sara (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2011)
Analysis of findings suggests that community unionism is vibrant within Mozambique. Trade union engagement with the main community organization representing the informal economy appears to be a key element of its revitalization strategy; both parties are benefiting from the relationship, and it appears to be sustainable. However, certain questions arise regarding its longer-term viability. Firstly, ASSOTSI represents those working illegally, while the OTM focuses on workers in formal employment. Secondly, OTM has a close relationship with the government due to its socialist past, yet ASSOTSI has a more tentative relationship with the government. Thirdly, ASSOTSI represents only African workers. Furthermore, senior figures in the OTM now seem to be re-considering the value of sustaining an affiliate model that includes all of the informal economy (including both owners and workers), and instead are contemplating setting up a union to represent informal sector workers.This article draws on in-depth research to investigate how community unionism has been employed in Mozambique, an emerging economy in Africa. In doing so, it asks whether engagement with community organizations is characterized by a strategic or piecemeal approach, the degree to which there are mutual benefits for the trade union and the community organization, and whether the relationship is sustainable in the longer term.Against the background of liberalization, privatization and financial crisis, unions face a declining number of core members. In emerging economies such as Mozambique, the formal sector now constitutes around eight percent of the working population, while around seventy-five per cent of the workforce is in the informal sector, with the remainder being unemployed. In many countries, unions have sought to engage these workers through “community unionism.”